2011
DOI: 10.3109/09593985.2011.608114
|View full text |Cite
|
Sign up to set email alerts
|

From idealistic helper to enterprising learner: Critical reflections on personal development through experiences from Afghanistan

Abstract: There is little written about the cultural, social, and ethical challenges encountered by physiotherapists engaging in development work. This article takes a critical perspective on what it means to engage in development work as an expatriate physiotherapist, through a self-critical reflection on experiences from Afghanistan. The field notes from an ethnographic study of a development project conducted in Afghanistan were analysed to explore the transformative process of personal and professional development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…While this model was historically used to describe learning by individuals, it has more recently been deployed to account for collective learning in organisations where the emphasis is on the creation of transformative learning, rather than transmission learning [ 32 , 33 ] This shift in approach from individuals, describes how learning emerges in institutionally situated activity and how higher mental functions arise from collective forms of behaviour, and from ‘multivoicedness’, where contradictions and dissonance are thought of as a creative source of change and development [ 34 ].
Figure 1 Harré’s [ 17 , 18 ] two-dimensional space based on Vygotsky’s ideas on assisted performance.
…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While this model was historically used to describe learning by individuals, it has more recently been deployed to account for collective learning in organisations where the emphasis is on the creation of transformative learning, rather than transmission learning [ 32 , 33 ] This shift in approach from individuals, describes how learning emerges in institutionally situated activity and how higher mental functions arise from collective forms of behaviour, and from ‘multivoicedness’, where contradictions and dissonance are thought of as a creative source of change and development [ 34 ].
Figure 1 Harré’s [ 17 , 18 ] two-dimensional space based on Vygotsky’s ideas on assisted performance.
…”
Section: Methodsmentioning
confidence: 99%
“…This problem-oriented view of the ‘new arrival’ tends to privilege public regimes of justification [ 9 ]. Some recent studies have embraced instead a more extended idea of induction of health care professionals as a process of acclimatisation and learning through ‘regimes of familiarity’ [ 16 ] ‘critical reflective processes’ [ 14 ], the ‘enterprising learner’ [ 17 ] and notions of growing ‘entrustability’ [ 18 ] all of which draw on situated and social process models of adaptation and learning in new environments. These have in common a call for comprehensive and expanded organisational support over longer periods of time [ 14 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…My frustration associated with the health system that I was a part of had negatively affected my inspiration toward work. 18 In addition, my role in the multidisciplinary team shows that my obligation is associated with intraoperative nursing rather than postoperative advocacy. If I work across boundaries, it might lead to conflicts between multidisciplinary teams; 19 thus, I would comfort myself that maybe it should not be my personal responsibility to care for postoperative patients.…”
Section: Informmentioning
confidence: 99%
“…There is limited scientific literature discussing this issue, as it is most likely an emerging issue with the recent increase in global mobility making these opportunities more readily available. Initial research conducted by Raymond and Hall suggested that motivations for volunteer tourism included: 28 wanting to feel that they contributed something; wanting to be distinguished from a tourist; wanting a sense of connection to the other ; and a desire to experience real poverty. It was identified that these trends are problematic as it objectifies the other , and may become socioeconomic/poverty voyeurism and a commodification of people.…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…It is important that the GLP model promotes student interest and facilitates the development of well-meaning students from idealistic helper to enterprising learner. 28 It is important to encourage and support genuine interest by students participating in these placements, as overseas opportunities may have positive outcomes in developing cultural understanding and global citizenship. 26 Additionally the learning opportunities for both local and visiting students and academics and the establishment of global networks promote collaborations and the advancement of the UN SDGs into the future.…”
Section: Ethical Considerationsmentioning
confidence: 99%